2016
DOI: 10.1182/blood-2015-03-635599
|View full text |Cite
|
Sign up to set email alerts
|

Brca1 deficiency causes bone marrow failure and spontaneous hematologic malignancies in mice

Abstract: • Brca1 deficiency causes Fanconi anemia-like cytopenias, mitomycin C hypersensitivity, and spontaneous bone marrow failure.• Brca1 is critical for the maintenance of normal hematopoietic progenitor function and genomic stability in the bone marrow.BRCA1 is critical for maintenance of genomic stability and interacts directly with several proteins that regulate hematopoietic stem cell function and are part of the Fanconi anemia (FA) double-strand break DNA repair pathway. The effects of complete BRCA1 deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 21 publications
3
41
0
Order By: Relevance
“…A fraction (27%; 7/26) of the Vav1-iCre;Brca1 F22-24/F22-24 mice that survived beyond 3 months of age did become moribund (hunched, immobile, cold) prior to death and developed lymphocyte infiltrated splenomegaly (Figure S2a). Unlike the prior report that found p53 mutations in some spleens that were Brca1 null (Vasanthakumar et al, 2016), when we used RNA-seq to analyze for mutations in expressed genes, only wild type p53 was found in these enlarged spleens. However, consistent with the same report, T-cell infiltration was present based on a decreased B-cell specific gene expression and an increased T-cell gene expression pattern in the enlarged spleens (Figure S2b).…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…A fraction (27%; 7/26) of the Vav1-iCre;Brca1 F22-24/F22-24 mice that survived beyond 3 months of age did become moribund (hunched, immobile, cold) prior to death and developed lymphocyte infiltrated splenomegaly (Figure S2a). Unlike the prior report that found p53 mutations in some spleens that were Brca1 null (Vasanthakumar et al, 2016), when we used RNA-seq to analyze for mutations in expressed genes, only wild type p53 was found in these enlarged spleens. However, consistent with the same report, T-cell infiltration was present based on a decreased B-cell specific gene expression and an increased T-cell gene expression pattern in the enlarged spleens (Figure S2b).…”
Section: Resultsmentioning
confidence: 71%
“…However, consistent with the same report, T-cell infiltration was present based on a decreased B-cell specific gene expression and an increased T-cell gene expression pattern in the enlarged spleens (Figure S2b). These data suggest that deletion of Brca1 from mouse hematopoietic cells has the potential to promote the development of hematopoietic malignancies from surviving progenitors (Vasanthakumar et al, 2016). …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…It will be highly interesting to clarify why these patients do not (or tend not to) develop hematopoietic stem cell failure because patients belonging to FA-D1/N/ J/O/R/S all seem to have a similar pathophysiology due to HR deficiency. Of note, a recent study demonstrated that BRCA1 deficiency, specifically in mouse bone marrow, causes hematopoietic defects (Vasanthakumar et al 2016). …”
Section: The Core Hr Genes In the Fa Pathwaymentioning
confidence: 99%